PENGARUH KEAKTIFAN BERORGANISASI, MOTIVASI DAN KOMITMEN BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA JURUSAN MANAJEMEN ANGKATAN 2017 DAN 2018 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU - , Arwinence Pramadewi, Aisyah Putri Pratami , Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine and analyze the influence of student activity in the organization, learning motivation and commitment to student achievement both partially and simultaneously.  The research population is all students of the 2017 and 2018 Management Department of the Faculty of Economics and Business, University of Riau who actively participate in the organization as many as 218 people. Determination of the sample used the Slovin formula, so that the samples taken were 68 students. The results of  the study stated that the activeness of students in organizations, learning motivation and learning commitment partially and simultaneously affected learning achievement. The magnitude of the influence of student activeness in organizations, learning motivation and learning commitment to learning achievement is 0.831 or 83.10%. Keywords : Student Activeness in Organizations, Learning Motivation, Commitment, and Learning Achievement